1997
DOI: 10.1038/sj.onc.1200904
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus large T antigen-dependent DNA amplification

Abstract: DNA ampli®cation is a readily measurable indicator for genome destabilization. Contrary to normal senescing cells, those of most immortal or transformed cell lines are karyotypically unstable and permissive for ampli®ca-tion. Permissivity for ampli®cation can be generated by gene products of several DNA tumor viruses whereby their interaction with the tumorsuppressor protein p53 is important. p53 is the major protein involved in check point control of DNA damage. Polyomavirus large T antigen is also involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Although the CDE sequence resembles a binding motif for E2F, complexes forming at the CDE-CHR were distinctly different from those forming at a genuine E2F site, such as that of the mouse thymidine kinase promoter which was employed for comparison. Use of antibodies indicated that the latter complexes contained E2F4 and p130, in agreement with earlier results in arrested mouse 3T3 cells (37); in contrast, neither antibody provided evidence for an involvement of these proteins in complexes forming on the CDE-CHR. Although this again agrees with published results (14), the possibility cannot be excluded that a much more intricate structure of the protein complexes forming at the CDE-CHR compared with those at an E2F site does not allow sufficient access for antibodies to cause changes in the complex formation or its size (see Discussion).…”
Section: Vol 75 2001supporting
confidence: 78%
“…Although the CDE sequence resembles a binding motif for E2F, complexes forming at the CDE-CHR were distinctly different from those forming at a genuine E2F site, such as that of the mouse thymidine kinase promoter which was employed for comparison. Use of antibodies indicated that the latter complexes contained E2F4 and p130, in agreement with earlier results in arrested mouse 3T3 cells (37); in contrast, neither antibody provided evidence for an involvement of these proteins in complexes forming on the CDE-CHR. Although this again agrees with published results (14), the possibility cannot be excluded that a much more intricate structure of the protein complexes forming at the CDE-CHR compared with those at an E2F site does not allow sufficient access for antibodies to cause changes in the complex formation or its size (see Discussion).…”
Section: Vol 75 2001supporting
confidence: 78%
“…Although cytochalasin D and blebbistatin cause a relative doubling of chromosome number, the fact that these cells were originally tetraploid might have influenced our observations. Therefore, focus forming assays were repeated in the hyperdiploid cell line REF52 (average of 56 chromosomes/cell) [Stiegler et al, 1997]. REF52 cells behave very similarly to normal fibroblasts in at least two respects: (i) they require a cooperating oncogene to be transformed by Ras, (ii) they are unable to generate resistance to PALA, a feature closely associated with the normal functioning of p53-dependent pathways for growth arrest [Franza et al, 1986;Perry et al, 1992].…”
Section: Polyploidy and Transformation By Rasmentioning
confidence: 99%
“…It has been shown that loss, decrease in expression, or mutation of Rb2/p130 can be linked to various carcinomas (Cinti et Rb2/p130 is a member of the ''pocket'' protein family (pRb, p130, p107) of tumor suppressors. The members of the ''pocket '' protein family share a high degree of homology and control cell-cycle progression by binding to various members of the E2F family of transcription factors and histone deacetylase 1 (HDAC1), which enhances transcriptional repression (Paggi et al, 1996;Stiegler et al, 1997;Stiegler et al, 1998;Zhang et al, 2000;Zini et al, 2001;Tonini et al, 2002). During cell-cycle progression, Rb2/p130 becomes hyperphosphorylated by cyclin-dependent kinase (CDK) complexes, which then leads to the ubiquitination and eventual degradation of Rb2/p130 protein by the proteasome.…”
mentioning
confidence: 99%